Oleo essencial de Nectandra grandiflora na dieta de jundiá (Rhamdia quelen) antes e depois da hipóxia: estresse oxidativo e desempenho zootécnico - Descovi, Sharine Nunes (2021)
In the current scenario, the use of prophylactics based on natural products has been growing due to their biodegradable potential and lower risk of toxicity to animals and the environment. Studies prove that essential oils have positive effects on development, through improvements in physiological, metabolic, antioxidant, immunological levels and even in the zootechnical performance of some species of fish when added to the diet. The aim of this study was to evaluate the effect of adding the essential oil of Nectandra grandiflora (OENG) to the diet of young jundiás and its relationship to the growth and pro and antioxidant parameters of this species during hypoxia and reoxygenation. 225 young jundiás (0.92 ± 20 g; 4.42 ± 50 cm) received a diet supplemented with OENG in the proportions: 0; 0.5; 1.0; 1.5 and 2.0 mL/kg of feed for 60 days and subsequently submitted to hypoxia for 8 hours and reoxygenation for 2 hours. Water quality parameters were monitored and maintained at levels acceptable for the species until the time of hypoxia (dissolved oxygen: 2 mg/L). Samples of liver, muscle and gills were collected, as well as measures of weight and length of the animals for further metabolic and performance analysis, respectively. Regarding the zootechnical performance, the tested OENG levels did not significantly alter the growth of the fish. Regarding stress due to hypoxia and reoxygenation, the tested OENG levels did not show an antioxidant effect compared to the parameters evaluated.